2021
DOI: 10.1155/2021/2252832
|View full text |Cite
|
Sign up to set email alerts
|

Immune Mechanism, Gene Module, and Molecular Subtype Identification of Astragalus Membranaceus in the Treatment of Dilated Cardiomyopathy: An Integrated Bioinformatics Study

Abstract: Astragalus membranaceus has complex components as a natural drug and has multilevel, multitarget, and multichannel effects on dilated cardiomyopathy (DCM). However, the immune mechanism, gene module, and molecular subtype of astragalus membranaceus in the treatment of DCM are still not revealed. Microarray information of GSE84796 was downloaded from the GEO database, including RNA sequencing data of seven normal cardiac tissues and ten DCM cardiac tissues. A total of 4029 DCM differentially expressed genes wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 101 publications
(107 reference statements)
0
1
0
Order By: Relevance
“…Additionally, AM administration increased the level of AKT1 protein in turn. Thus, we supposed that the regulation effect on lipid metabolism by AM might be associated with the endocrine resistance pathway through AKT1 [ 41 ]. We also found that AM administration significantly increased the level of CCND1 protein in the liver tissue and WAT of HFD-fed mice.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, AM administration increased the level of AKT1 protein in turn. Thus, we supposed that the regulation effect on lipid metabolism by AM might be associated with the endocrine resistance pathway through AKT1 [ 41 ]. We also found that AM administration significantly increased the level of CCND1 protein in the liver tissue and WAT of HFD-fed mice.…”
Section: Discussionmentioning
confidence: 99%